Access to credit for vulnerable people: An emerging market investigation - Bui, Huu Toan; Le, Ngoc Thang (International Journal of Innovative Research and Scientific Studies, 2025)
This paper addresses the limited access to formal credit among vulnerable rural households in Vietnam—a persistent challenge despite the government’s efforts to promote financial inclusion. The research aims to identify key socio-economic determinants that affect the ability of vulnerable groups to access official credit channels. Using data collected from a survey of 1,200 rural households across eight provinces representing Northern, Central, and Southern Vietnam, the study employs a binary Logit regression model to estimate the probability of successful credit access. The findings reveal that the highest education level within a household and household income positively influence access to formal credit. In contrast, the education level of the household head, land ownership status, and residence in the Central region negatively affect the likelihood of receiving loans. These results underline the complexity of credit accessibility in rural areas and suggest that improving financial literacy and revising legal frameworks are essential to enhance credit outreach. The paper concludes with policy recommendations to strengthen the legal and institutional foundations for inclusive credit programs tailored to the needs of Vietnam’s vulnerable populations.